The Effectiveness of the Project-Based Learning Model Assisted by Artificial Intelligence on the Listening Skills of Indonesian Language Education Students - Deby Luriawati Naryatmojo; Bambang Hartono; Diyamon Prasandha; Dyah Prabaningrum; Aldi Dwi Saputra (JTP - Jurnal Teknologi Pendidikan, 2026)
The integration of technology in Indonesian language learning has continued to develop alongside advances in Artificial Intelligence (AI), although its application in classroom practice remains limited. This study aims to examine the effectiveness of the Project-Based Learning (PjBL) model assisted by Artificial Intelligence in improving the listening skills of Indonesian Language Education students. The study employed a quasi-experimental design with two groups: an experimental group consisting of 23 students who received AI-assisted PjBL instruction and a control group consisting of 34 students who received conventional instruction. In the experimental group, AI was implemented through the use of speech-to-text tools and AI-based audio generators to support listening activities. Data were collected through pretests and posttests measuring listening skills, supported by observation and documentation. Data analysis included descriptive statistics, paired sample t-tests, independent sample t-tests, and N-gain analysis. The results showed that the AI-assisted PjBL model significantly improved students’ listening skills. The experimental group achieved a higher mean score compared to the control group, with an N-gain score of 0.42 (moderate category), while the control group obtained an N-gain score of 0.21 (low category). These findings indicate that AI-assisted PjBL is more effective than conventional learning methods in enhancing listening skills. This study implies that integrating AI into project-based learning can support more interactive and meaningful listening instruction and contribute to the development of students’ language skills in higher education contexts.